PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS KAHOOT PADA MATERI RUANG LINGKUP BIOLOGI SMA/MA X - Nur Baetina (Universitas Majalengka, 2021)
Globalization and technology have developed rapidly. The world of education also feels the developments that are happening. One of them makes it easier for educators to develop kahoot-based learning media, especially in the scope of biology. Kahoot is an alternative interactive learning media by emphasizing learning styles that involve the active participation of students. This study aims to develop kahoot-based learning media in the biology scope of SMA / MA X. This study uses the research and development (R&D) method with the ADDIE model and uses a sample of 3 students as validators and 10 students as respondents. The results showed that the validation value of kahoot learning media was feasible to use. The kahoot learning media was able to attract the attention of students and the average score of the media trial for 10 students was 82. Kahoot learning media based on digital game-based learning were able to attract students in a learning process that was not boring. This can be seen from the results of media trials in table 2 and in graph 1 students' perceptions of kahoot learning media with digital game based learning.